The impact of destructive leadership on turnover intention among Chinese technology professionals: the mediating role of job burnout and the moderating role of regulatory emotional self-efficacy - Chen, Songqing; Wang, Shuli; Wu, Jun (Frontiers in Psychology, 2025)
IntroductionDestructive leadership is conceptualized as a social job demand that depletes employees’ psychological resources. Drawing on the Job Demands–Resources (JD–R) theory, we tested the mediating role of job burnout in the link between destructive leadership and turnover intention, and the moderating effect of regulatory emotional self-efficacy (RESE) on the direct path from destructive leadership to turnover intention.MethodsWe analyzed survey data from 403 Chinese technology professionals using validated scales. Further, we tested whether job burnout mediates the link between destructive leadership and turnover intention, and whether RESE weakens the direct association between destructive leadership and turnover intention.ResultsDestructive leadership and turnover intention were positively associated. Job burnout partially mediated this link (significant indirect effect), and RESE attenuated it; simple-slope tests revealed a weaker association for employees with higher RESE.ConclusionThe findings position destructive leadership as a resource-depleting social demand within JD–R, confirming burnout as a proximal mechanism linking it to turnover intention, and identifying RESE as a psychological buffer of the direct pathway. Organizations should deter destructive leadership and strengthen employees’ RESE to sustain wellbeing and mitigate talent loss in high-pressure technology settings.